2022
DOI: 10.3390/nano12213909
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, Mechanical and Tribological Properties of Arc Ion Plating NbN-Based Nanocomposite Films

Abstract: NbN, NbN-Ag and NbN/NbN-Ag multilayer nanocomposite films were successfully deposited by an arc ion plating system (AIP), and their microstructures, mechanical and tribological properties were systematically investigated. The results show that all the films had a polycrystalline structure, and the Ag in the Ag-doped films existed independently as a face-centered cubic phase. The content of Ag in NbN-Ag and NbN/NbN-Ag films was 20.11 and 9.07 at.%, respectively. NbN films fabricated by AIP technique had excelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…They found that the optimal addition of Ag (9 at%) shows low friction and improved wear resistance at HT (600 °C ) due to the formation of Ag and AgCrO2 (as seen in Figure 7e). Similarly, various studies have revealed that the optimal concentration of soft/noble metals in primary ceramic hard coatings has a beneficial effect on elevated temperature applications [104][105][106][107]. Similar observations on Cu incorporated into AlTiVN coatings using HIPIMS demonstrated that the friction (0.45) and wear resistance (10−16 m 3 /N⋅m) were significantly enhanced at the optimum Cu concentration of 10.7 at% at high temperature (600 °C ), as reported by Mei et al [99].…”
Section: Figure 6 (A)mentioning
confidence: 99%
“…They found that the optimal addition of Ag (9 at%) shows low friction and improved wear resistance at HT (600 °C ) due to the formation of Ag and AgCrO2 (as seen in Figure 7e). Similarly, various studies have revealed that the optimal concentration of soft/noble metals in primary ceramic hard coatings has a beneficial effect on elevated temperature applications [104][105][106][107]. Similar observations on Cu incorporated into AlTiVN coatings using HIPIMS demonstrated that the friction (0.45) and wear resistance (10−16 m 3 /N⋅m) were significantly enhanced at the optimum Cu concentration of 10.7 at% at high temperature (600 °C ), as reported by Mei et al [99].…”
Section: Figure 6 (A)mentioning
confidence: 99%